2016
DOI: 10.15199/48.2016.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Problems and solutions in the introduction of wireless communication technology to the clinical medicine setting

Abstract: The introduction of wireless communication technology into large Japanese hospitals is rapidly progressing. However, many hospitals are having problems, such as inadequate signal range, electromagnetic interference by waves generated inside/outside the hospital, or by devices carried in by the staff or patients, and some have problems with network security. Here we show illustrations of these problems and give solutions that might be considered. Streszczenie. Wprowadzanie technologii komunikacji bezprzewodowej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It can be observed that the behaviour of radio signals is very different in the underground mines compared to that in outdoor and line of sight environments. In addition, the first step in increasing a wireless network performance is understanding the actual environment [16]. A systematic analysis is to investigate the effects of various underwater channel conditions, resulting from changing the water turbidity levels, on video quality and when different modulation techniques have been imposed [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be observed that the behaviour of radio signals is very different in the underground mines compared to that in outdoor and line of sight environments. In addition, the first step in increasing a wireless network performance is understanding the actual environment [16]. A systematic analysis is to investigate the effects of various underwater channel conditions, resulting from changing the water turbidity levels, on video quality and when different modulation techniques have been imposed [17].…”
Section: Literature Reviewmentioning
confidence: 99%